(untitled) (Research, Society and Development, 2022)
The present study aimed to evaluate the mortality by malignant neoplasm of the cervix in the state of Ceará from 2014 to 2019 and to found the epidemiological profile. This is retrospective,exploratory, quantitative and descriptive epidemiological study with data collection from the Mortality Information System (SIM), obtained from the website of the Departamento de Informática do Sistema Único de Saúde (DATASUS), with observation of the variables:year of death, age group, education color/race and place of occurrence. Data processing was done using Microsoft Word 2013 software and the TabNet Win32 program, version 3.0. In total,1757 deaths by CC were reported, and the years 2017, 2018 and 2019 were the ones wuith the most records, with and índex of 18,4%, 17,7% and 18,0%, respectively. Women Who spent 1 to 3 years 476 (27,1%) in a school environment were the most affeted. As for the places of occurrence,the hospital environment was more prominent whith (1048) 59,6% of notifications. Still, 73,6% were of mixed race/color and women aged 50 to 69 years were the most affected. The growing number of notifications shows that screening measures and socio-educacional campaigns have been carried out more regularly, however, the number of deaths demonstrates that these measures must be intensified, since it is na easily diagnosed disease, and if identified early at the rate of mortality decreases considerably.